2023
DOI: 10.3389/ti.2023.11206
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Women in Contemporary Kidney Transplant Trials

Abstract: Women are often underrepresented in clinical trials. It is unclear if this applies to trials in kidney transplant (KT) and whether the intervention or trial focus influences this. In this study, the weighted participation-to-prevalence ratio (PPR) for women enrollees in KT trials was determined for leading medical transplant or kidney journals between 2018 and 2023 using meta-regression overall and in three sensitivity analyses by: 1) Whether the intervention involved immunosuppression; 2) Area of trial focus;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“… 24 RCTs among dialysis populations found that women made up 40% of participation, whereas women are understudied in kidney transplantation trials, and both studies revealed underreporting of sex or gender subgroup analyses. 20 , 25 Notably, there was no available data on how many women and men were approached and declined to be included in the trials, a possible future consideration to improve disparities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 RCTs among dialysis populations found that women made up 40% of participation, whereas women are understudied in kidney transplantation trials, and both studies revealed underreporting of sex or gender subgroup analyses. 20 , 25 Notably, there was no available data on how many women and men were approached and declined to be included in the trials, a possible future consideration to improve disparities.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 , 44 However, gaps remain with women underrepresented in national conferences and academic grant rounds, receiving fewer achievement awards, and are less likely to be listed as first author. 20 , 25 , 36 , 45 , 46 , 47 , 48 These disparities can contribute to women being left out of leadership roles and can impact their growth and promotion. One possible barrier contributing to this underrepresentation is the presence of additional responsibilities for women, such as caregiving and parental leave, which may hinder their ability to fully engage in networking opportunities and research promotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, only 33.7% of participants in 24 KTR trials were women, suggesting underrepresentation of women in kidney transplantation trials, including ones examining cardiometabolic risk [ 58 ]. A more balanced representation of women in these trials will contribute to further exploring and understanding of gender disparities in posttransplant care.…”
Section: Sex Disparities In Mortality In Men and Women With Ckdmentioning
confidence: 99%
“…We further suggest that in the preclinical realm, increasing female sex and diverse gender representation in all kidney transplantation research and reporting of sex and/or gender disaggregated data are additional crucial steps toward gender equity. 9 In addition to acknowledging the obstacles to full participation in discussions and referral for kidney transplantation in women living with kidney disease, concrete steps using gendersensitive communication tools and strategies are required, similar to those recommended for increasing kidney research engagement with women and genderdiverse populations. 10 So, in answer to the question: Why do nephrologists seek kidney transplantation for their patients?…”
mentioning
confidence: 99%